An investigation of antecedents and outcomes of accounting information quality: Evidence from SMEs - Ayke Nuraliati; Ayi Astuti; Tamy Ali Januarty; Ahmad Johan; Dedi Sudarmadi (Jurnal Akuntansi dan Auditing Indonesia)
In an increasingly competitive business era, quality accounting information is a crucial factor for companies that want to achieve better performance, especially for small and medium-scale manufacturing industries. The quality of accounting information not only affects internal decision-making, but also shapes the trust of stakeholders, including investors, creditors, and business partners. This study aims to identify the role of innovation capability, riskiness, moral standard, knowledge management, management accounting system and accounting information quality on financial performance. This study used 318 questionnaires distributed to general managers, financial managers, chief accountants and internal auditors) in manufacturing sector industrial companies in Bandung City which were selected randomly. Then, the data was tested using the SEM-PLS approach to test the relationship between the variables studied to obtain accurate results. The results of this study indicate that innovation capability, riskiness, moral standards, and knowledge management have a significant effect on the management accounting system and the quality of accounting information. Likewise, the management accounting system and the quality of accounting information have a significant effect on financial performance. Given these results, this study recommends to company management the importance of implementing modern mais because it has become an important component, and it is difficult to achieve competitive advantage and survive in the market without relying on a good system.